Uncovering the roles of PINK1 and parkin in mitophagy - Matsuda, Noriyuki (Landes Bioscience, 2010)
Parkinson disease (PD) is the second most prevalent neurodegenerative disorder, and thus elucidation of the pathogenic mechanism and establishment of a fundamental cure is essential in terms of public welfare. Fortunately, our understanding of the pathogenesis of two types of recessive familial PDs—early-onset familial PD caused by dysfunction of the PTEN-induced putative kinase 1 (PINK1) gene and autosomal recessive juvenile Parkinsonism (ARJP) caused by a mutation in the Parkin gene—has evolved and continues to expand.